Multi-Hop Signal Transmission Patterns in Oracle APEX-Based Monitoring Systems with Dynamic IoT Feedback Loops - Keshireddy, Srikanth Reddy (International Journal of Engineering, Science and Information Technology, 2025)
This investigation maps how multi-hop signals travel through Oracle APEX monitoring architectures while absorbing real-time feedback from distributed IoT devices. It reproduces, in code, the relay of packets between nodes and sketches the tilt of delivery rates when loss, spacing, and retransmission limits shift with the network load. The platform weaves SAP telemetry with Honeycomb Oracle APEX dashboards and MQTT feedback loops, then pours those streams into a simulation engine that spits out curves for signal sag, loop latency, and feedback turnaround. Raw numbers show that tuning the retransmit count and watching hop-length can swing reliability figures almost one-to-one, while edge-smart loops clipped jitter delays by a claimed twenty-two percentage points. This work leaves behind a timed model for picking the quickest feedback paths in cloud-flavoured enterprise IoT setups, hoping to give digital overseers a snappier and more elastic toolkit than they had yesterday.